An ART score to note objectively the quality of an ART procedure. (February 2018) - Labrune, Elsa; Mery, Lionel; Lornage, Jacqueline; Aknin, Isabelle; Guérin, Jean François; Benchaib, Mehdi
Abstract: Objective: To construct an ART score to evaluate an ART procedure before the result (pregnancy or not), and to provide objective data in discussions with couples in the decision to discontinue further attempts. Study design: A retrospective multicentrique study was performed. The ART score was constructed using data from the MediFirst © database used in our center. The development of the score was conducted on a sample of 507 in vitro fertilization cycles carried out between January 2011 and July 2011. Model calibration and determination of the discrimination capacity of the ART score were performed with 4463 cycles in our center and 1369 cycles from an external ART center. The ART score was validated temporally and geographically with clinical pregnancy and take home baby rate. Results: The ART score was obtained from data from both partners and ART procedure. The ART score was segmented into four classes depending on the clinical pregnancy rate. There was a linear relationship between the ART score and clinical pregnancy rate (r = 1.0, p < 0.001). The ART score was validated temporally and geographically. Conclusion: An objective ART score has been constructed and validated. It will be of help to ART teams and it is an objective tool to explain to a couple the choices for the next ART attempt.